MIDWIFERY CARE MANAGEMENT FOR MRS. D IN PHYSIOLOGICAL POSTPARTUM PERIOD WITH LOW BREAST MILK SUPPLY AT PMB RIYANTI BANGETAYU KULON GENUK, SEMARANG CITY, CENTRAL JAVA PROVINCE IN 2024 - Widianti, Tia; Febriana Sari; Riyanti; Haura Nabila; Miranda Hutagaol; Mastaida Tambun; Ester Simanullang, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
The postpartum phase begins immediately after the delivery of the infant and placenta, spanning approximately six weeks. During this window, the maternal reproductive system undergoes "involution," a process where organs gradually return to their pre-gestational state. This period is a high-risk transition for both the mother and the newborn; statistically, 60% of maternal complications leading to death occur post-delivery, with half of those fatalities happening within the initial 24 hours. Consequently, rigorous monitoring is vital to mitigate mortality rates. In the case of Mrs. D, a physiological postpartum assessment revealed limited lactation but no pathological indicators such as mastitis, abscesses, or malignancies. The diminished milk supply was attributed to insufficient suckling stimulation rather than underlying illness. Ultimately, the 2024 case study at PMB Bd. Riyanti confirms that Mrs. D’s recovery followed a normal trajectory, with vital signs remaining stable and the clinical management aligning perfectly with established midwifery theories.